2009
DOI: 10.1172/jci38660
|View full text |Cite
|
Sign up to set email alerts
|

Human PTRF mutations cause secondary deficiency of caveolins resulting in muscular dystrophy with generalized lipodystrophy

Abstract: Caveolae are invaginations of the plasma membrane involved in many cellular processes, including clathrinindependent endocytosis, cholesterol transport, and signal transduction. They are characterized by the presence of caveolin proteins. Mutations that cause deficiency in caveolin-3, which is expressed exclusively in skeletal and cardiac muscle, have been linked to muscular dystrophy. Polymerase I and transcript release factor (PTRF; also known as cavin) is a caveolar-associated protein suggested to play an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
288
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(303 citation statements)
references
References 40 publications
12
288
0
1
Order By: Relevance
“…The functions of caveolins are closely linked to a family of cytoplasmic proteins termed cavins (Hill et al 2008;Bastiani et al 2009;Hansen et al 2009;McMahon et al 2009). PTRF/ cavin-1 is essential for the formation of caveolae (Hill et al 2008;Liu et al 2008) and, like caveolin, has been shown to be associated with LD function and lipid storage in cultured adipocytes (Aboulaich et al 2006), mice (Liu et al 2008), and human patients (Hayashi et al 2009;Rajab et al 2010). …”
Section: Interactions With Caveolae Caveolins and Cavinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of caveolins are closely linked to a family of cytoplasmic proteins termed cavins (Hill et al 2008;Bastiani et al 2009;Hansen et al 2009;McMahon et al 2009). PTRF/ cavin-1 is essential for the formation of caveolae (Hill et al 2008;Liu et al 2008) and, like caveolin, has been shown to be associated with LD function and lipid storage in cultured adipocytes (Aboulaich et al 2006), mice (Liu et al 2008), and human patients (Hayashi et al 2009;Rajab et al 2010). …”
Section: Interactions With Caveolae Caveolins and Cavinsmentioning
confidence: 99%
“…Genetic mutation of LD-related proteins such as, seipin (Magre et al 2001), caveolin-1 (Kim et al 2008), PTRF/cavin1 (Hayashi et al 2009;Rajab et al 2010), and 1-acylglycerol-3-phosphate-O-acyltransferase 2 (Agarwal et al 2002), which is a critical enzyme in TG and phospholipid synthesis, has been shown to cause lipodystrophies. The mechanism that seipin mutation leads to lipodystrophy may not be directly related to its effect on LD formation because it also affects a transcriptional cascade that drives adipogenesis (Payne et al 2008;Chen et al 2009).…”
Section: Lipid Droplets and Disease Diseases Related To Lipid Storagementioning
confidence: 99%
“…It is therefore to be expected that the loss of this protein should disrupt adipose tissue function, both through impairments in fatty acid uptake, and thus TAG synthesis, and (more speculatively) through the loss of insulin signalling into the cell (Cohen et al 2003, Saltiel & Pessin 2003. In addition, mutations in PTRF (encoding polymerase 1 and transcript release factor, also known as cavin-1) have recently been identified in several kindreds with an autosomal recessive disorder characterised by generalised lipodystrophy and muscular dystrophy , Hayashi et al 2009). Unlike BSCL2 and AGPAT2 mutations, in which somatic overgrowth is a common feature, CAV1 defects were associated with short stature (albeit in a single kindred so far).…”
Section: Substrate Availabilitymentioning
confidence: 99%
“…29,49 Caveolin 3-deficient myoblasts formed thin myotubes upon activation of the TGF-b effector, Smad2. 29 Activated Smad2 was also observed in skeletal muscle from patients with muscular dystrophy with generalized lipodystrophy caused by deficiency of cavin, an assembly molecule for caveolin 3.…”
Section: Discussionmentioning
confidence: 99%
“…29 Activated Smad2 was also observed in skeletal muscle from patients with muscular dystrophy with generalized lipodystrophy caused by deficiency of cavin, an assembly molecule for caveolin 3. 49 To confirm the novel concept of the caveolin 3-TGF-b-p21 axis in the pathobiology of muscle atrophy, further characterization of both satellite cells and myoblasts will be required in skeletal muscle samples from patients with LGMD1C and cavin 1 deficiency.…”
Section: Discussionmentioning
confidence: 99%